Effect of Washing Bays on Water Quality of Rivers: A Case Study of River Rurigita Muko Sub-County Rubanda District Uganda. - Monday, Innocent (Kabale University, 2025)
Water plays a significant role in maintaining human health and is a fundamental need for all living organisms. The overall purpose of the study was to assess the water quality of river Rurigita and its suitability for human consumption. The specific objectives were; to identify factors that affect water quality parameters in River Rurigita, determine the levels of water quality parameters, and compare the values of the water quality parameters with allowed WHO limits. In the study from different sampling sites. Ten (10) water samples were collected and analyzed for physical, chemical, and biological water quality parameters using standard methods. Data generated was entered in SPSS and Microsoft Excel for analysis along river Rurigita. Findings established the major factors affecting water quality parameters of river Rurigita were; trucks, motorcycles, small car, and cloth washing, solid waste disposal, and town run-offs. The findings indicated a high level of pH (8.22), turbidity (11.2 NTU), TSS (747 mg/L), BOD 980 mg/L, COD 600 mg/L, and the presence of very dangerous heavy metals; Cd (0.000 3mg/L), Hg (0.0002 mg/L) and Pb (0.00 2mg/L). Biological water quality indicated contamination of river Rurigita with both Total coliform (83.3 CFU) and E. coli (28.3 CFU) an indicator of animal or human fresh fecal contamination exposing the communities to waterborne diseases. Water quality parameters such as PH (8.22), turbidity (11.2 NTU) total coliform, and E. coli were above the W.H.O. permissible limits. Vehicle wash activities and women washing clothes in the upstream of river Rurigita should be regulated to protect the communities from waterborne diseases.